Quality of life of patients treated with radiotherapy - Rożniecka-Hełmińska, Adrianna; Karolina Maniak, Diana; Kupcewicz, Ewa (Journal of Education, Health and Sport, 2018)
Abstract: Radiotherapy is one of the most commonly used anticancer treatments. Despite continuous technological development it may cause adverse symptoms, and as a result reduce the quality of life in patients undergoing radiation therapy. Objective of the work: Analysis of the quality of life of patients treated with radiation therapy and the effect determination of selected factors and their clinical complications on the quality of life of oncological patients. Material and methods: The study included 100 patients diagnosed with cancer, including 47 (47%) women and 53 (53%) men, with an average age of 62.1 (± 9.47) years. The study used a standardized questionnaire EORTC QLQ-C30, in assessing the quality of life of cancer patients and a questionnaire of our own design containing sociodemographic and clinical data. The collected empirical data were analyzed statistically. The level of significance was p <0.05. Results: In the group of patients tested the average rate the overall quality of life was 50.5 (± 16.28) with a median of 50. The highest quality of life in the test reported in the field of cognitive functioning, and the lowest in the area of social functioning. In 72% of patients experienced complications of radiotherapy. During the analysis, it was found that the overall quality of life and functioning in all domains is lower comparing to the results of patients with no side effects of treatment. The analysis also found that in patients with head and neck cancer, which are irradiated at the same area, the level of cognitive functioning is significantly lower than the level of functioning in the same domain patients irradiated in the chest area (p <0.008) and in the area of reproductive organs (p <0.007). Conclusions: There is a diversity of quality of life of patients with and without complications of treatment with ionizing radiation, which have a significant impact on the quality of life of cancer patients. Location area irradiated during radiotherapy has a significant impact on the quality of life of patients. Treatment with radiation therapy adversely affects the quality of life of patients.